The Motives of Canadian Baptist Women Missionaries to India, 1905–1910 - Cherian, Binu Binoy (My University, 2025)
During the colonial period, namely in the late nineteenth and early twentieth centuries, Canadian Baptist women missionaries had a notable impact in India. Their association with imperial authority was intricate and diverse, shaped by their religious undertaking and the broader political circumstances of British colonial governance in India. Canadian Baptist women missionaries were motivated by a fervent evangelical passion to propagate Christianity in India. The missionaries participated in educational and social reform endeavours in India. They founded educational institutions, orphanages, and medical centres, offering schooling and medical care to Indian women and children. Although the Canadian Baptist women missionaries had humanitarian intents, they were frequently perceived as catalysts of cultural imperialism. This research is based on the work of Canadian Baptist missionaries in India between 1905 and 1910, much before Indian Independence (1947), and it will demonstrate that Canadian Baptist women missionaries had several interrelated motives, central being the betterment of the people.